FIRB intercropping of vegetables and seed spices with wheat for higher productivity and profitability of small and marginal farmers - Tripathi, Subhash Chandra; Chander, Subhash; Meena, Raj Pal (Journal of Cereal Research, 2017)
A field experiment was conducted for two consecutive years commencing from 2014-2015 to 2015-2016 at ICAR-Indian Institute of Wheat and Barley Research, Karnal, Haryana, India to assess the productivity and profitability of vegetables and seed spices intercropping with wheat under bed planting. Pooled analysis showed that radish planted on bed recorded maximum wheat equivalent yield (113.55 q/ha), which was significantly higher than all other treatments. Among the intercrops, wheat on bed +radish in furrow produced maximum wheat equivalent yield (92.46 q/ha), which was 36.37 % higher than sole wheat crop. This was followed by wheat + turnip intercrop with 77.98 q/ha wheat equivalent yield. Growing of other four intercrops like wheat + cauliflower, wheat + cabbage, wheat + coriander, wheat + fenugreek was not feasible in furrows probably owing to shading effect of wheat crop. Maximum net return obtained in sole radish crop on bed followed by wheat on bed + radish in furrows intercrop, which was 96.5% and 27.4% higher than sole wheat crop, respectively. Therefore, selective vegetables can be easily grown in furrows under bed planted wheat, which will be boon to small and marginal farmers. Â Doi.org/ 10.25174/2249- 4065/2017/73366